Effect of hydrogen addition on exergetic performance of gas turbine engine. Issue 2 (1st November 2019) - Gunasekar, P.; Manigandan, S.; S., Venkatesh; Gokulnath, R.; Vimal, Rakesh; Boomadevi, P.
Abstract : Purpose: The depletion of fossil fuel and emissions of harmful gases forced the pioneers in search of alternate energy source. The purpose of this study is to present an effective use of hydrogen fuel for turbojet engines based on its exergetic performance. Design/methodology/approach: This study was performed to measure the assessment of exergetic data of turbojet engines. Initially, the test was carried out on the Jet A-1 fuel. Then, a series of similar tests were carried out on turbojet engines with hydrogen fuel to measure their performance results. Finally, the exergetic values of both were compared with each other. Findings: The introduction of hydrogen fuel reduced the exergy efficiency, and a 10 per cent reduction was observed in exergy efficiency. Simultaneously, the waste exergy rate increased by 9 per cent. However, because of the high specific fuel exergy, hydrogen fuel was better than Jet A-1 fuel. Note that parameters such as environmental effect factor and ecological effect witnessed an increase in their index owing to the addition of hydrogen. Practical implications: Introduction of alternative blends is necessary for achieving lower emission of gases such as CO, NOx and CO2 from gas turbine engines without compromising on performance. The Jet A fuels were replaced by blends to obtain better emission characteristics. Originality/value: The use of hydrogen in turbojet engines showed an adverse effect on exergetic performance. However, it was very impressive to see a 200 per cent reduction in emissions. From the comparison of exergy efficiency results of inlet, combustion and nozzle, it is evident that the combustion chamber has the largest values of exergy ratio, waste exergy ratio, cost flow, ecological factor, environmental factor and fuel ratio owing to irreversibility in the combustion process.